Psychiatric Symptoms in Women with High-risk Pregnancy in the Postpartum Period: A Case-control Study - Zahra Basirat; Fatemeh Ramaezani; Mahdi Sepidarkish; Mahdi Kashifard; Mahbobeh Faramarzi (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective: Psychiatric symptoms are common mental issues in pregnancy and the postpartum period. There is limited information regarding the psychiatric symptoms of women with high-risk pregnancy in the postpartum period. This study aimed to compare the severity of psychiatric symptoms and psychological distress in women with high-risk and low-risk pregnancies in the postpartum period. Methods: This case-control study examined 250 women in the postpartum period in two groups with low-risk (n = 112) and high-risk (n = 138) pregnancies. Women completed the Brief Symptom Inventory-53 (BSI-53) and the Risk Postnatal Psychosocial Depression Risk Questionnaire (PPDRQ). Results: The mean severity of psychiatric symptoms in women with high-risk pregnancies was significantly higher than that in women with low-risk pregnancies (39.34 ± 17.51 vs. 30.26 ± 17.08). Additionally, the frequency of psychological distress in women with high-risk pregnancies was approximately twice higher than that in women with low-risk pregnancies (30.3% vs. 15.2%). Furthermore, the risk factors for depression in women with high-risk pregnancies were almost 1.5 times (59.8% vs. 39.8%) higher than the factors in women with low-risk pregnancies. The results of the logistic analysis indicated that high-risk pregnancies could be twice the odds ratio of developing postpartum psychological distress (ß = 2.14, 95% CI 1.4-6.3, p= 0.036). Conclusion: Psychiatric symptoms and the psychological distress index are higher in postpartum women with high-risk pregnancies than in postpartum women with low-risk pregnancies. The study suggests that obstetricians and pregnant women's health care providers should strongly consider screening of psychiatric symptoms in women with high-risk pregnancies both during pregnancy and after delivery as the women's routine care priorities.